REDUCING SIX BIG LOSSES THROUGH TECHNICAL AND DIGITAL INTEGRATION TO IMPROVE OVERALL EQUIPMENT EFFECTIVENESS (OEE) ON A CARTONER MACHINE IN A PHARMACEUTICAL COMPANY - Maukar, Anastasia Lidya; Hanum, Dinda Latifah (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2025)
Improving Overall Equipment Effectiveness (OEE) On Cartoner Machine Using Six Big Losses In Pharmaceutical Company.This research aims to improve the Overall Equipment Effectiveness (OEE) of the Cartoner machine at a pharmaceutical manufacturing facility in Cikarang, Indonesia. The main problem identified was low availability, primarily caused by frequent leaflet jams and delays in spare part replacement. Root cause analysis using Fishbone Diagrams and Pareto Charts revealed that leaflet jams contributed 67% of unplanned downtime.The study applied the Six Big Losses framework, focusing on downtime reduction. Two improvements were implemented. Technically, the suction system was redesigned to enhance leaflet handling and make a form for complaint to the supplier. Digitally, a Spare Parts Inventory Management System was developed using Microsoft Power Apps, enabling real-time stock monitoring, automated alerts, and faster spare part requests. After implementation, OEE improved from 75.36% to 81.90%, and availability increased from 76.94% to 83.62%. This research demonstrates that combining technical upgrades with digital tools can significantly reduce unplanned downtime and enhance production efficiency.